Quinine: Past, Present, and Future Perspective in Malaria and Autoimmune Disorder - Mohd. Wasiullah; Piyush Yadav; Abhishek Kumar Yadav (International Journal of Pathogens, 2025)
Quinine, a natural alkaloid extracted from the bark of the cinchona tree, has traditionally played a key role in treating malaria, a disease caused by parasites of the Plasmodium genus. Since its discovery in the 17th century, quinine has evolved from a rudimentary treatment to an essential component of modern antimalarial therapies. This article explores the historical use of quinine in the fight against malaria, its role in current treatment regimens, and its future applications. In addition, we review emerging evidence suggesting the utility of quinine in autoimmune disorders, such as systemic lupus erythematosus and rheumatoid arthritis, where its immunomodulatory effects may provide new avenues for treatment. Although the role of quinine in the treatment of malaria remains indispensable, resistance to its use is increasing, requiring a move towards alternative drugs and combined therapies. At the same time, the growing understanding of quinine’s impact on immune regulation paves the way for its repurposing in the management of autoimmune diseases. This review provides an overview of quinine’s historical importance, its current role in medicine, and its promising future in therapies for malaria and autoimmune diseases.
Keywords: Malaria; autoimmune disorders; cinchona officinalis; herbal medicine; quinine